THE EFFECT OF STANDING WATER TO THE VALUE OF BRITISH PENDULUM NUMBER (BPN) ON ASPHALTIC CONCRETE â WEARING COURSE SURFACE - Aryansah Pratama Putra, Willy
Skid resistance is the roughness of the road surface layer resulting from the combination of microtexture and macrotexture of a road surface. For vehicles with low speeds, the value of microtexture is more important while for vehicles with high speeds, the value of macrotexture becomes more important to be considered in preventing skidding. Aquaplaning is a phenomenon of the formation of a layer of water between the road surface and vehicle tires due to standing water on the road surface which can result in loss of friction between the tires and the road surface so that the vehicle slips and cannot be controlled. The main purpose of this study was to evaluate the effect of standing water on the value of the British Pendulum Number of the road surface on the AC-WC pavement and to identify the height of the standing water that the British Pendulum Number could measure properly using the British Pendulum Tester. In this study, the microtexture value was measured using the British Pendulum Tester under normal conditions and standing water occurred. From the test results, it is known that the BPN value of the pavement decreases when there is a standing water until the water level reaches 3 mm. When the water reaches a height of 5 mm, the BPN value is actually higher than the results of the previous test. This indicates that skid resistance testing using the British Pendulum Tester is no longer relevant to be carried out because the pendulum rubber is first held back by existing water so that the test equipment cannot optimally access the surface texture of the test object.